Statistical media optimization for the production of clinical uricase from Bacillus subtilis strain SP6 - Sneha O. Pustake; Prashant K. Bhagwat; Padma B. Dandge (Heliyon, 2019)
In this study, a potent uricase producing organism was isolated by a thorough screening and identified as Bacillus subtilis strain SP6 by using 16s rDNA sequencing. Response surface methodological optimization was employed for the enhanced production of uricase from newly isolated Bacillus subtilis strain SP6. In media optimization studies, Plackett Burman (PB) design was used for the selection of the critical media components; which were further optimized using central composite design (CCD). Lactose, soya peptone, uric acid and FeSO4.7H2O were found to be the critical factors influencing the enzyme production. Optimum uricase production with these factors was deduced using central composite design. Significant level of the factors were 12.2 g/L of lactose, 12.79 g/L of soya peptone, 2.55 g/L of uric acid and 0.00325 g/L FeSO4.7H2O. Use of statistical optimization upsurges uricase yield from 1.2 U/ml to 15.87 U/ml enhancing the overall production by 13.23 fold; which confirms that the model is effective for process optimization.